Anaerobic biological treatment of industrial saline wastewater: fixed bed reactor performance and analysis of the microbial community structure and abundance. Issue 13 (6th June 2020) - Jeddi, Mariem; Karray, Fatma; Loukil, Slim; Mhiri, Najla; Ben Abdallah, Manel; Sayadi, Sami
ABSTRACT: The purpose of the present work is to treat saline Tuna fish wastewater, with the salt concentration of 43 g L −1 and total organic carbon (TOC) of 8.3 g L −1, using an anaerobic fixed bed reactor involving salt-tolerant bacteria from the natural hypersaline environment during 150 days. The highest volatile solids (VS) removal efficiency of 84.1% was recorded for the organic loading rate (OLR) of 1.04 g TOC L −1 .d −1 and the lowest salinity of 14.6 g NaCl L −1 . In addition, the maximum biogas production of 0.8 L −1 .d −1 for a working volume of 4 L and an organic loading rate of 2.07 g TOC L −1 .d −1 correlated with the decrease of Volatile fatty acids (VFA) content. The Polymerase Chain Reaction-Denaturing Gradient Gel Electrophoresis (PCR-DGGE) and the phylogenetic analysis of the bacterial community showed the action of hydrolytic, acidogenic, halotolerant sulfate-reducing and halophilic fermentative bacterium during the processing time. A stable archaeal and methanogenic community's diversity including hydrogenotrophic methanogens was demonstrated with Quantitative-PCR (Q-PCR). The highest bacterial population abundance was detected for 1.45 g TOC L −1 .d −1 and the important methanogenic community abundance for 2.07 g TOC L −1 .d −1 may be related to the highest biogas production in this charge for an effluent salinity of 27.7 g NaCl L −1 . GRAPHICAL ABSTRACT: